2017
DOI: 10.1371/journal.pone.0178223
|View full text |Cite
|
Sign up to set email alerts
|

Various meteorological conditions exhibit both immediate and delayed influences on the risk of stroke events: The HEWS–stroke study

Abstract: We hypothesized that meteorological conditions on the onset day and conditions on the former days may play important roles in the modulation of physical conditions. Associations of meteorological factors and their changes in former days with stroke onset are of interest. We conducted a multicenter retrospective study to evaluate the frequency of stroke events and their interaction with meteorological conditions and their daily changes. Acute stroke patients (n = 3935, 73.5±12.4 years, 1610 females) who were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Air temperature (T) and atmospheric pressure (AP) are among the most closely studied weather variables; increases, decreases, and fluctuations in both have been significantly linked to numerous stroke subtypes. A statistically significant negative association has been observed between T and the incidence of ischaemic stroke (IS) [ 6 8 ], haemorrhagic stroke (HS) [ 9 , 10 ], intracerebral haemorrhage [ 11 14 ]], and subarachnoid haemorrhage [ 15 17 ]. The results of a meta-analysis [ 4 ] have also shown a negative association between daily T and all stroke subtypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Air temperature (T) and atmospheric pressure (AP) are among the most closely studied weather variables; increases, decreases, and fluctuations in both have been significantly linked to numerous stroke subtypes. A statistically significant negative association has been observed between T and the incidence of ischaemic stroke (IS) [ 6 8 ], haemorrhagic stroke (HS) [ 9 , 10 ], intracerebral haemorrhage [ 11 14 ]], and subarachnoid haemorrhage [ 15 17 ]. The results of a meta-analysis [ 4 ] have also shown a negative association between daily T and all stroke subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown both a negative association [ 1 , 12 , 18 ] and a positive association [ 14 , 15 , 19 ] between the risk of stroke and AP. Studies conducted predominantly in Europe have shown an increase in the incidence of stroke associated with AP changes, adjusting for T or seasonality [ 19 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] In addition, ICH increases when the thermohydrological index (THI) gets extremely cooler in 4 days prior. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Air temperature (T) and atmospheric pressure (AP) are among the most closely studied weather variables; increases, decreases, and uctuations in both have been signi cantly linked to numerous stroke subtypes. A statistically signi cant negative association has been observed between T and the incidence of ischaemic stroke (IS) [6][7][8], haemorrhagic stroke (HS) [9,10], intracerebral haemorrhage [11][12][13][14] ], and subarachnoid haemorrhage [15][16][17]. The results of a meta-analysis [4] have also shown a negative association between daily T and all stroke subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown both a negative association [1,12,18] and a positive association [14,15,19] between the risk of stroke and AP. Studies conducted predominantly in Europe have shown an increase in the incidence of stroke associated with AP changes, adjusting for T or seasonality [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%